Revaluación del activo fijo como práctica contable que permite incrementar el valor en libros del patrimonio a valor de mercado - Requelme Díaz, Marjorie Viviana (2015)
The present work has as main objective to assess the revaluation of fixed assets as an accounting practice that allows to increase the book value of assets to market value. As we have chosen factors fixed assets, the ratio of the book value of the assets and the market value, both aggregates, and term structure of interest rates. The main idea is to guide the company to appropriate organization within the accounting department and identify the main problems that arise, affecting them directly to equity. For example, a module for entry and registration of acquirers of fixed assets with constant reports of the company, among others. Our research shows us about the revaluation of fixed assets as an accounting practice that allows to increase the book value of assets to market value, so we'll get the perfect formula for the stabilization of our company. In conclusion this research is of great help to the company, because in this way he is being guided by experts to optimize the carrying amounts of assets so we proceeded to apply the general accountant. My recommendation would include more useful models for proper operation in the accounting system and to make comparisons between the results obtained.